Ego Functions, Defenses, and Countertransference: A Beginning School Social Work Student’s Way to Professional and Personal Growth - Hili Tsarfati (International Journal of School Social Work, 2017)
The school social worker is often challenged by the complexity of the child-school-family paradigm, where the therapeutic relationship is one of the most central parts of treatment. Through this relationship, social workers attempt to recognize their clients’ internal conflicts as well as their clients’ relationships with others. In this paper the writer examines the perceptions and reality of the versatile role of the school social worker. She reflects upon, describes, and analyzes her therapeutic relationship with Monique, one of her more challenging cases during her first year as a social worker in training placed at an alternative high school in Brooklyn, New York. Monique presented with many internal challenges and external crises that required professional attention, including extensive trauma. The writer also explores her own countertransference, which made the therapeutic relationship personally challenging. Finally, by describing the development of both the professional and personal relationships, the writer illustrates how important it is to continuously reflect on the practitioner’s own feelings and experiences. Critical self-awareness, she suggests, can contribute to the strengthening of the therapeutic connection, and further the development of a school social worker’s practice skills, such as mindfulness, compassion and competence.
Keywords: transference; countertransference; ego functions; adolescents; school social work intern; school social work clinical practice